Az európai parlamenti választások eredményei, az újonnan megválasztott Európai Parlament megalakulása - Szekrényes, Éva (Közép-Európai Közlemények, 2014)
The aim of the study is to present the European Parliamentary elections taking place on 22%25 May 2014. The first part of the study focuses on the results, the Europeans and the Hungarian as well. The turnout was almost the same as last elections in 2009, but the balance of power has been shifted slightly. The political groups have remained almost the same like before. The European People’s Party lost several mandates, the Socialists and the Greens managed to maintain almost the same size of group with a small loss, while the liberals lost the biggest. The European Conservatives became the third biggest political group in the newly elected European Parliament. The left wing parties are also the winners of this election: the GUE/NGL succeeded to gain several new seats. The study also shows how the newly elected European Parliament (EP) held its inauguration session. The first step was the formation of the different political groups. Then, during its inauguration session held in Strasbourg, the new members of the parliament elected the President, the 14 Vice-Presidents, and the quaestors. In addition, the essay gives a short outlook to the ongoing institutional changes, mainly concentrating on the new European Commission.